2003
DOI: 10.1046/j.1470-6431.2003.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Shopping orientation segments: exploring differences in store patronage and attitudes toward retail store environments among female apparel consumers

Abstract: The purpose of this study was to identify shopping orientation segments for US female consumers. The sample included 151 women, aged 18 years and over. This research examined differences in the segments relative to store patronage preferences (i.e. department, discount, specialty), attitude toward the environment of the store selected as first choice when shopping for a specific apparel item (i.e. a dress), and demographic characteristics. Cluster analysis revealed that four shopping segments described the fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 19 publications
1
70
1
1
Order By: Relevance
“…Based on these findings, four levels of sophistication in demand sensing are summarized in Table 5. Segmenting stores according to the demand pattern is a common practice [56] and influences how stocks are deployed. Depending on the granularity, three levels of sophistication are identified in deploying stock according to segmentation (Table 6).…”
Section: Demand Sensing and Segmentationmentioning
confidence: 99%
“…Based on these findings, four levels of sophistication in demand sensing are summarized in Table 5. Segmenting stores according to the demand pattern is a common practice [56] and influences how stocks are deployed. Depending on the granularity, three levels of sophistication are identified in deploying stock according to segmentation (Table 6).…”
Section: Demand Sensing and Segmentationmentioning
confidence: 99%
“…Moye and Kincade (2003) [20] segmented American female apparel consumers, and found that members in the higher income group pursue their ability and reputation, but members in the lower income group Sustainability 2017, 9, 1012 3 of 12 look for bargains or do not hesitate to make a purchase if they like the good. These groups choose different kinds of stores as well.…”
Section: Shopping and Leisure Behaviors By Gender Age And Incomementioning
confidence: 99%
“…In particular, fashionshopping orientation is a general purchasing behavior form encompassing psychological and behavioral aspects that appear when purchasing fashion items (Choi, 2015;Kim & Rhee, 2004;Lee & Ku, 2011;Park & Na, 2003). It provided the additional insight for the customer behavior pattern and was treated as an important variable influencing fashion store patronage as well as fashion product and store choice (Moye & Kincade, 2003).…”
Section: Fashion-shopping Orientationmentioning
confidence: 99%